Does constipation affect the effectiveness of washed microbiota transplantation in treating autism spectrum disorders? - Pan, Zihao; Gao, Zheng; Chen, Junyi; Quan, Yongxi; Xu, Jiating; Liang, Xiaofeng; Xie, Wenrui; He, Xingxiang; Wu, Lihao (Frontiers in Neuroscience, 2025)
PurposeWashed microbiota transplantation (WMT) has been shown to improve the symptoms of Autism Spectrum Disorder (ASD). It’s currently unclear whether the presence of constipation affects the efficacy of WMT in children with ASD. This study aims to investigate whether constipation affects the efficacy of WMT in children with ASD.Patients and methodsTo investigate the efficacy of WMT for ASD, we conducted a retrospective analysis of changes in ASD-related symptoms, sleep disturbances, gastrointestinal manifestations, intestinal barrier integrity, and gut microbiota composition in 103 ASD patients undergoing WMT. They were divided into two groups according to whether constipation was present or not before treatment.Results1. Aberrant Behavior Checklist (ABC), Childhood Autism Rating Scale (CARS), and Sleep Disturbance Scale for Children (SDSC) scores in the non-constipation and constipation groups decreased with an increase in the number of WMT treatments. 2. Comparison of two groups: ABC scores in the non-constipation group decreased more after the first WMT course, whereas ABC scores in the constipation group decreased more after two WMT courses. 3. Intestinal Barrier Function: D-lactate levels decreased more in the constipation group after the first two courses. In general, WMT treatment had no significant effect on intestinal barrier function in patients with ASD. 4. Effect of WMT on constipation: As the number of WMT courses increased, Bristol Stool Form Scale (BSFS) scores in constipation group gradually approached 4. 5. Constipation group had lower microbial diversity than non-constipation group at baseline. After one course of WMT, constipation group showed an obvious increase in microbial diversity and a significant increase in the relative abundance of Bifidobacteria compared to non-constipation group.ConclusionPost WMT, core symptoms and sleep disorders were significantly improved in both groups. Feces returned to normal shape in the constipation group. A difference in efficacy between the two groups was observed in early stages, but after multiple courses of WMT no difference in efficacy was noted. Although in the short-term, children with ASD and comorbid constipation showed a significant increase in microbial diversity after receiving WMT, mid-term outcomes indicate that constipation does not affect the efficacy of WMT in treating ASD.